2010
DOI: 10.1039/c0ce00048e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of uracil derivatives: the crucial role of weak fluorine–fluorine noncovalent interactions

Abstract: We have recently communicated the important role of lone pair-p, p-p and hydrophobic interactions in the solid architecture of 5-fluoro-1-hexyluracil and 1-hexyluracil (CrystEngComm, 2010, 12, 362-365). As a matter of fact, the simple substitution of a hydrogen atom by a fluorine atom has an enormous consequence in the solid state structure. It has been demonstrated that this is due to an increase in the p-acidity of the ring. In this article we extend the study to other uracil derivatives, where we have chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…The results suggested that the tetrameric motif having four type II F···F interactions provides 4 kcal/mol stabilization to the crystal packing (hence each contributed approximately 1 kcal/mol stabilization energy). Atoms in molecule (AIM) approach for this tetrameric motif confirmed the presence of (3, −1) BCPs and the value of [112] the Laplacian was observed to be positive, suggesting that these were closed shell interactions. Similar results have been obtained from related experimental charge density studies [113][114][115].…”
Section: Insight Into Halogen-halogen Interactions Involving Fluorinesupporting
confidence: 72%
See 1 more Smart Citation
“…The results suggested that the tetrameric motif having four type II F···F interactions provides 4 kcal/mol stabilization to the crystal packing (hence each contributed approximately 1 kcal/mol stabilization energy). Atoms in molecule (AIM) approach for this tetrameric motif confirmed the presence of (3, −1) BCPs and the value of [112] the Laplacian was observed to be positive, suggesting that these were closed shell interactions. Similar results have been obtained from related experimental charge density studies [113][114][115].…”
Section: Insight Into Halogen-halogen Interactions Involving Fluorinesupporting
confidence: 72%
“…However there are examples where F···F interactions have played a crucial role in the crystal packing. For example, in case of a uracil derivative, the F···F interactions were observed to be important in crystal packing [112]. In the crystal packing of (N′-(3-hydroxypropyl)-5-fluorouracil, a tetramer assembly of molecules held together by the presence of four type II F···F interactions was observed ( Fig.…”
Section: Insight Into Halogen-halogen Interactions Involving Fluorinementioning
confidence: 94%
“…[39] We have recently reported that the combination of a nucleobase (uracil) with a long aliphatic chain leads to a very interesting solid-state architecture that resembles a lipid bilayer. [40] The hydrogen-bond donor/acceptor capability of the nucleobase is responsible of the formation of a 2D hydrogen-bonding network that nicely stacks with another 2D layer through π-π interactions. Hydrophobic interactions between the aliphatic chains are responsible for the final architecture.…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive factor that changes this behaviour is the presence of the fluorine atom at C(5) position of uracil ring, which forces a zigzag disposition of the layer due to the crucial role of FÁÁÁC@O interaction between fluorine and the p-system of uracil [23][24].…”
Section: Introductionmentioning
confidence: 98%